Restoration of Epithelial Sodium Channel Function by Synthetic Peptides in Pseudohypoaldosteronism Type 1B Mutants - Willam, Anita; Aufy, Mohammed; Tzotzos, Susan; Evanzin, Heinrich; Chytracek, Sabine; Geppert, Sabrina; Fischer, Bernhard; Fischer, Hendrik; Pietschmann, Helmut; Czikora, Istvan; Lucas, Rudolf; Lemmens-Gruber, Rosa; et al. (Frontiers in Pharmacology, 2017)
The synthetically produced cyclic peptides solnatide (a.k.a. TIP or AP301) and its congener AP318, whose molecular structures mimic the lectin-like domain of human tumor necrosis factor (TNF), have been shown to activate the epithelial sodium channel (ENaC) in various cell- and animal-based studies. Loss-of-ENaC-function leads to a rare, life-threatening, salt-wasting syndrome, pseudohypoaldosteronism type 1B (PHA1B), which presents with failure to thrive, dehydration, low blood pressure, anorexia and vomiting; hyperkalemia, hyponatremia and metabolic acidosis suggest hypoaldosteronism, but plasma aldosterone and renin activity are high. The aim of the present study was to investigate whether the ENaC-activating effect of solnatide and AP318 could rescue loss-of-function phenotype of ENaC carrying mutations at conserved amino acid positions observed to cause PHA1B. The macroscopic Na+ current of all investigated mutants was decreased compared to wild type ENaC when measured in whole-cell patch clamp experiments, and a great variation in the membrane abundance of different mutant ENaCs was observed with Western blotting experiments. However, whatever mechanism leads to loss-of-function of the studied ENaC mutations, the synthetic peptides solnatide and AP318 could restore ENaC function up to or even higher than current levels of wild type ENaC. As therapy of PHA1B is only symptomatic so far, the peptides solnatide and AP318, which directly target ENaC, are promising candidates for the treatment of the channelopathy caused disease PHA1B.